비대칭 잠제 주변의 파고 및 흐름의 3차원적인 수리특성에 관한 수치모의 - 이우동(Woo-Dong Lee); 허동수(Dong-Soo Hur); 서성부(Sung-Bu Suh) (Han-guk haeyang gonghak hoeji (Online), 2011)
In case of constructing submerged breakwaters for the purpose of preventing coastal erosion, the number of submerged breakwaters, as well as their asymmetry is dependent on the field conditions. The aim of the present study was to examine the 3-D hydrodynamic characteristics (3-D wave field, wave height, mean water level, and mean flow) around the asymmetric submerged breakwaters using a 3-D numerical model, LES-WASS-3D, which was validated through a comparison with existing experimental data and showed fairly nice agreement. From the numerical results, the wave height, mean water level, and mean flow are discussed in relation with the variation in the breakwater length ratio.